2009
DOI: 10.1111/j.1468-0459.2009.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of synoptic scale weather systems on sub‐surface soil temperatures in a diurnal frost environment: preliminary observations from sub‐antarctic marion island

Abstract: . Marion Island in the South Indian Ocean has a maritime climate dominated by diurnal frost processes in the landscape. We test the hypothesis that synoptic time‐scale measurements are essential in understanding the drivers of diurnal frost processes. Preliminary results from automated microclimate measurements in a polar desert habitat show that diurnal soil surface temperatures on Marion Island are influenced by a complex interaction of radiation balance, air mass circulation, cloud cover and snow. The passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Recent preliminary results show that at the microscale diurnal soil surface temperatures on Marion Island are influenced by a complex interaction of radiation balance, air mass circulation, cloud cover and snow (Nel, Boelhouwers et al 2009). Effective nocturnal cooling to below freezing point has historically been reported to depend on clear, windless nights (Outcalt 1971) and soil frost on Marion Island also appears dependent on clear skies (Nel, Boelhouwers et al 2009), with frequencies ranging from 60 to over 200 days per year in a climate dominated by strong winds, cloud cover and high soil moisture values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent preliminary results show that at the microscale diurnal soil surface temperatures on Marion Island are influenced by a complex interaction of radiation balance, air mass circulation, cloud cover and snow (Nel, Boelhouwers et al 2009). Effective nocturnal cooling to below freezing point has historically been reported to depend on clear, windless nights (Outcalt 1971) and soil frost on Marion Island also appears dependent on clear skies (Nel, Boelhouwers et al 2009), with frequencies ranging from 60 to over 200 days per year in a climate dominated by strong winds, cloud cover and high soil moisture values.…”
Section: Discussionmentioning
confidence: 99%
“…Effective nocturnal cooling to below freezing point has historically been reported to depend on clear, windless nights (Outcalt 1971) and soil frost on Marion Island also appears dependent on clear skies (Nel, Boelhouwers et al 2009), with frequencies ranging from 60 to over 200 days per year in a climate dominated by strong winds, cloud cover and high soil moisture values. Misty and overcast conditions are associated with maritime temperate air mass and westerly circulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the leeward migration typically observed in feldmark plants, Boelhouwers et al (2003) reported A. selago cushions migrating toward the prevailing wind as a result of decay of the cushions on the leeward side where needle ice forms. On Marion Island, frost events are predominantly associated with southwesterly airflows (Nel et al, 2009). Macquarie Island is likely to experience a similar regime given the similarities in synoptic weather patterns and soil temperatures between it and Marion Island, and thus windblown ice is likely associated with southwesterly winds.…”
Section: Correspondence Of Distortion To Wind Regimesmentioning
confidence: 99%